(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Postpartum Haemorrhage (PPH) is one of the leading causes of global maternal mortality. It requires multidisciplinary approach for early recognition, intervention and prevention. Objective: The aim of the study was to evaluate the incidence, intervention, and outcome of patients with PPH admitted to the ICU. Methods: This retrospective observational study was conducted in the multidisciplinary ICU of Enam Medical College and Hospital, Savar, Dhaka, Bangladesh from January 2018 to December 2019. All the patients with PPH who were admitted to the ICU were the study population. Data about primary admission or referral case, mode of delivery, condition on admission, causes of admission, intervention, duration of ICU stay, and the outcome were collected and analyzed. Results: Total 1986 patients were admitted to ICU during the study period. Among them, obstetric patients were 152(7.65%).Total 39 (25.65%) cases were identified as PPH. Their mean age was27.23±4.98 years. 82.05%patients were referred from other hospitals and 17.94% primarily admitted to this hospital. 66% undergone vaginal delivery whereas 34% undergone cesarean section. Causes of admission were due to placental abnormalities (23.07%), followed by retained placenta (20.51%), genital tract trauma (17.94%), grand multipara (12.82%), uterine atony (12.82%), ruptured uterus (7.69%) and fibroid uterus (5.12%).Most of the patients presented with tachycardia, SOB, severe anaemia, shock or hypotension, desaturation, poor GCS and fluid overload. Regarding intervention, 64.1% patients received oxygen supplementation, 35.89% patients received mechanical ventilation, 94.87% patients received blood and blood products, 69.23% cases received inotropes, 35.89% received uterine tamponade, 82.05% cases received uterotonics, 33.33% cases received antifibrinolytics, bimanual uterine compression was given for 48.71% cases, uterine blood clot was removed for 43.58% cases, repair of genital tract tear was done for 17.94% cases, uterine artery ligation was done for 7.69% cases, arterial blood gas analysis and central venous cannulation was done was done for all the patients. Hysterectomy was conducted for 23.07% cases. The mean duration of ICU stay was 2.23 ±1.61 days and maternal mortality was 20.51%. Conclusion: PPH is one of the most common causes of obstetric ICU admission which requires multidisciplinary approach. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):79-83